2018
DOI: 10.5812/jjcdc.59474
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Blood Group and Colon Cancer in Shiraz Namazi Hospital During 2002 - 2011

Abstract: Background: Cancer is the second cause of death in the world and the third in Iran. Colorectal cancer is the third fatal cancer in the world. Objectives: Blood group and its RH are among the genetic factors that can be associated with colon cancer. This study was performed with the aim of investigating the relationship between blood group and colon cancer. Methods: This study was undertaken in cases of colon cancer that referred to Namazi hospital from 2002 to 2011. The required data were gathered using a chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It was reported that there are various associations between particular ABO phenotypes and an increased susceptibility to disease [3] . For example, gastric cancer is found to be more common in blood group A individuals, whereas gastric and duodenal ulcers or Schizophrenia occur more commonly among the O blood group individuals [7] , while Rh antigens were reported to be a risk factor of different diseases such as noise-induced hearing loss (NIHL) [8] . Some epidemiological studies demonstrated significant association between the "ABO" blood group and the risk of diabetes mellitus.…”
mentioning
confidence: 99%
“…It was reported that there are various associations between particular ABO phenotypes and an increased susceptibility to disease [3] . For example, gastric cancer is found to be more common in blood group A individuals, whereas gastric and duodenal ulcers or Schizophrenia occur more commonly among the O blood group individuals [7] , while Rh antigens were reported to be a risk factor of different diseases such as noise-induced hearing loss (NIHL) [8] . Some epidemiological studies demonstrated significant association between the "ABO" blood group and the risk of diabetes mellitus.…”
mentioning
confidence: 99%
“…As a result of another study done in the USA, there was no clear correlation between ABO and the risk of CRC 14 .…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, Kashfi et al reported a significant relationship between blood group and colon cancer (P < 0.05), and the highest rate of colon cancer was reported among those with blood group O+ (48.7%), Rh+ (90.4%), and male patients (60.4%) [26]. Urun et al reported that ABO/Rh blood groups were significantly associated with CRC risk and that there was no relationship between K-ras status and the ABO blood group and Rh factor [20].…”
Section: Discussionmentioning
confidence: 94%